al-Baruni, Za‘ima Sulayman (1910–1976) - Ashour, Radwa; Ghazoul, Ferial; Reda-mekdashi, Hasna (Arab Women Writers: A Critical Reference Guide, 1873-1999, 2008)
Libyan literary pioneer and short-story writer born in Jadu, located in Libya’s western mountains. She is the daughter of anti-colonial fighter Sulayman al-Baruni. She received her early education in Turkish in Istanbul and then returned to Libya, where she completed her studies in the field of Arabic. She witnessed the various phases of her father’s struggle and after his death settled in Tripoli. She worked in education after Libyan independence and published her literary works in Libyan newspapers and magazines. She collected and edited critical editions on her father’s life and poetry. She participated in the Afro-Asian Women’s Conference held in Cairo in 1960.
Keywords: Biographies – Djebel Nefousa – 20e siècle